Pathologic Conditions of the Human Nervous and Muscular Systems Associated with Mutant Chaperones: Molecular and Mechanistic Aspects - Everly Conway de Macario; Alberto J. L. Macario (Frontiers Media SA, 2021)
This eBook presents illustrative examples of genetic chaperonopathies affecting primarily nerves and muscles and discusses molecular mechanisms and treatment targeting chaperones, i.e., chaperonotherapy.